Democratic Republic of the Congo : Interim Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report, 2004)
This paper focuses on the Democratic Republic of the Congo's (DRC) Interim Poverty Reduction Strategy Paper (I-PRSP) Preparation Status Report. DRC's I-PRSP is based on three fundamental pillars, namely: peace and good governance, which are considered to be the essential condition for the strategy to succeed; stabilization and pro-poor growth; and support for grassroots initiatives. The involvement of the development partners, civil society, and the private sector has been strengthened, resulting in better participation. Nevertheless, the process has been delayed by the slowness of the provision of human and financial resources.